A case of a primary myelofibrosis with progression and related literature review of progression phase genetics. (20th July 2021) - Chen, Dong; Fuda, Franklin; Weinberg, Olga
Abstract: Philadelphia (BCR‐ABL)‐negative myeloproliferative neoplasms (MPNs) include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). MPN can transform into an accelerated or a blast phase, which is associated with poor response to standard therapy and low overall median survival. We present an interesting case of a patient with a history of PMF and progression and summarize the current studies on genetic features of myeloproliferative neoplasms in blast phase (MPN‐BP) with an emphasis on PMF. Although MPN‐BP show ≥20% blasts in peripheral blood or bone marrow, it is not considered as acute myeloid leukemia (AML) according to the WHO classification. While MPNs‐BP typically lack genetic mutations seen in de novo AML, they commonly harbor IDH1/2, SRSF2, ASXL1, and TP53 mutations, similar to the genetic profiles of acute myeloid leukemia with myelodysplasia‐related changes (AML‐MRC).